A família Rubiaceae juss. na vegetação ripária de um trecho do alto rio Paraná, Brasil, com ênfase na tribo Spermacoceae. - Pereira, Giovana Faneco (2007)
The family Rubiaceae was described for Antoine Laurent de Jussieu, at 1789, and includes plants with various habits, like trees, shrubs, herbs, climbers and rarely epiphytes. Their characteristics are, mainly, simple and opposite or sometimes whorled leaves; interpetiolar, rarely intrapetiolar stipules; stamens usually as many as the corolla lobes, nearly always fixed on the corolla tube; and inferior ovary. It is mainly distributed in the tropical regions of the South America. In Brazil, it is more represented in the Atlantic Forest, mainly, within the shrubs. It is one of the largest angiosperm families, and consist of about 637 genera and 10700 species. Taxonomic delimitations, mainly for subfamilies and tribes, it changed since the original descriptions, due to richness and variety of the morphological characteristics. It is one of the families with more floristic richness in the riparian vegetation of the Upper Paraná River floodplain, Paraná and Mato Grosso do Sul States, Brazil. The aims of this study were to show a checklist for species of Rubiaceae, with identification key, for the riparian vegetation of the Upper Paraná River floodplain. Were found 36 species and two varieties included in 26 genera, 10 tribes and four subfamilies.